Why do academics blog? An analysis of audiences, purposes and challenges - Mewburn, Inger; Thomson, Pat (New Zealand Science Review, 2014)
​Academics are increasingly being urged to blog in order to expand their audiences, create networks and to learn to write in more reader-friendly style. This paper holds this advocacy up to empirical scrutiny. A content analysis of 100 academic blogs suggests that academics most commonly write about academic work conditions and policy con-texts, share information and provide advice; the intended audience for this work is other higher education staff. We contend that academic blogging may constitute a community of practice in which a hybrid public/private academic operates in a ‘gift economy’. We note, however, that academic blogging is increasingly of interest to institutions, and this may challenge some of the current practices we have recorded. We conclude that there is still much to learn about academic blogging practices. Studies in Higher Education 38(8): 1105–1119 (2013)